2012
DOI: 10.1002/mus.23481
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of chemokines and their receptors in duchenne muscular dystrophy: potential for attenuation of myofiber necrosis

Abstract: Our data suggest a possible beneficial role for CXCR1/2/4 ligands in managing muscle fiber damage control and tissue regeneration. Upregulation of endothelial chemokine receptors and CXCL8, CCL2, and CCL5 expression by cytotoxic macrophages may regulate myofiber necrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
42
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 32 publications
(31 reference statements)
5
42
0
Order By: Relevance
“…Muscle biopsies from children with Duchenne muscular dystrophy (DMD) showed increased CCL2 in the endothelium, and CCL2 has been implicated in macrophage and t-cell recruitment in the DMD mdx mouse model. [26, 27] It is possible these changes reflect physiological responses to inflammatory infiltrates in FSHD participant muscles, but further studies will be required to elucidate the exact relationship of circulating proteins to muscle inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Muscle biopsies from children with Duchenne muscular dystrophy (DMD) showed increased CCL2 in the endothelium, and CCL2 has been implicated in macrophage and t-cell recruitment in the DMD mdx mouse model. [26, 27] It is possible these changes reflect physiological responses to inflammatory infiltrates in FSHD participant muscles, but further studies will be required to elucidate the exact relationship of circulating proteins to muscle inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Also, C-X-C motif chemokine ligands (CXCL) such as CXCL1, CXCL2, CXCL3, CXCL8, and CXCL11 for neutrophils contributing to the inflammatory phase during regeneration and absent from normal muscle fibers were induced in DMD myofibers 62. In addition, we found the secretion of macrophage migration inhibitory factor (MIF), an inflammatory cytokine and chemoattractant, was regulated by contraction in C2C12 myotubes 64.…”
Section: Potential Drugs Targeting Inflammatory Mechanisms In Dmdmentioning
confidence: 85%
“…We recently found that NF-κB is activated in C2C12 myotubes upon muscle contraction and upregulate C-C motif chemokine ligand (CCL) 2 secretion, inducing THP-1 monocyte chemoattraction 61. In addition, several CC chemokines including CCL2, which are the components of the largest family of chemokines, and chemoattractive for diverse inflammatory cells, showed increased expression in mdx muscle 62. These findings suggest that increased CCL2 secretion from DMD muscles may also contribute to monocyte chemoattraction into skeletal muscles.…”
Section: Potential Drugs Targeting Inflammatory Mechanisms In Dmdmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Chronic activation of signaling pathways involved in the inflammatory response further exacerbates dystrophic pathology by increasing myofiber expression of the major histocompatibility complex 18 and the secretion of chemokines and cytokines. 19 Although profibrotic signaling is initially activated in an attempt to repair compromised myofibers, it is susceptible to upregulation by the unremitting nature of muscle damage, which triggers fibrosis and perpetuates inflammation. 20 As the cellular mechanisms that govern these secondary responses are intimately linked, it is difficult to ascribe hierarchical order to the molecular events that exacerbate DMD pathogenesis.…”
Section: Introductionmentioning
confidence: 99%